SYNERGISTIC STRATEGY FOR FORMING AN ENLIGHTENED SOCIETY IN THE NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2025)
The article studies the theoretical and methodological foundations of the formation of an enlightened society in New Uzbekistan, the socio-philosophical aspects of the formation of an enlightened society in New Uzbekistan, the future tasks of the formation of enlightenment as a high moral value in New Uzbekistan. Also, the synergistic strategy of the formation of an enlightened society in New Uzbekistan is analyzed.